Plasma phospholipid profiling of a mouse model of anxiety disorder by hydrophilic interaction liquid chromatography coupled to high‐resolution mass spectrometry. (5th March 2018) - Berkecz, Róbert; Körmöczi, Tímea; Tömösi, Ferenc; Szegedi, Viktor; Horváth, János; Kovács, Nóra; Janáky, Tamás
Abstract: Glycerophospholipids (PLs), as amphipathic small molecules and the main constituents of biological membranes, play an important role in several cellular processes, even though their accurate identification from complex biological samples remains a challenge. In this paper, we report a fast and comprehensive HILIC‐ESI‐MS method for the analysis of glycerophospholipid classes using high‐resolution mass spectrometry in negative mode. The final method enabled the quantitative analysis of 130 endogenous PL species in mouse plasma. The application of the method developed was to find differences of plasma PL composition in a mouse model of anxiety disorder. In the case of four PL classes and 35 PL species, significant differences were observed comparing low anxiety‐related behavior with high anxiety‐related behavior groups. The most characteristic trend was up‐regulation in both the PL classes and PL species, and decreases were only detected in two phosphatidylcholines among 35 species in mice having elevated anxiety.